1993
DOI: 10.2307/2404269
|View full text |Cite
|
Sign up to set email alerts
|

Relative Abundance and Resistance Traits of Two Collembola Species Under Metal Stress

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. British Ecological Society is collaborating with JSTOR to digitize, preserve and extend access to Journal of Applied Ecology. Summary 1. Population differentiation was studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
2

Year Published

1994
1994
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 27 publications
(27 reference statements)
3
31
0
2
Order By: Relevance
“…Although the mode of action may vary between metals and species, observations on Onychiurus armatus have demonstrated that when fed copper-, copper/lead-, or copper/ zinc-contaminated fungi the reduced reproduction is due to a reduced number of eggs rather than the ability of the eggs to hatch. A similar mode of action may also be the case for the eect of nickel on reproduction in F. ®metaria (Bengtsson et al, 1985;Tranvik et al, 1993).…”
Section: Discussionmentioning
confidence: 64%
“…Although the mode of action may vary between metals and species, observations on Onychiurus armatus have demonstrated that when fed copper-, copper/lead-, or copper/ zinc-contaminated fungi the reduced reproduction is due to a reduced number of eggs rather than the ability of the eggs to hatch. A similar mode of action may also be the case for the eect of nickel on reproduction in F. ®metaria (Bengtsson et al, 1985;Tranvik et al, 1993).…”
Section: Discussionmentioning
confidence: 64%
“…Aporrectodea rosea (Savigny) and Allolobophora chlorotica (Savigny) appear to be more sensitive to metal contamination than L. rubellus or Lumbricus castaneus (Savigny), since these species are absent from soils containing -2800 pg g-1 Zn, whereas L. rubellus or L. castaneus survive in such soils. Species-specific responses to metal pollutants have been found in many groups of soil invertebrates including earthworms Morgan 1988, 1991), isopods (Hopkin, 1990;Jones and Hopkin 1991;Hopkin et al 1993) and Collembola (Bengtsson and Rundgren 1988;Tranvik and Eijsackers 1989;Tranvik et al 1993). These results indicate that it is important to adopt a species-specific approach in ecotoxicological studies (Van Straalen and Ernst 1991;Hopkin 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Collembola also have been used to improve the International Organization for Standardization (ISO) standard test (Fountain & Hopkin, 2001;Crouau et al, 1999). Many studies have been conducted in relation to Collembola sensitivity and resistance to pollutants in populations exposed to longterm contamination of soils, in particular to heavy metals (Posthuma, 1990;Posthuma et al, 1992;Tranvik et al, 1993).…”
Section: Soilmentioning
confidence: 99%